Rural policy, rural quangos – searching for clarity in West Dorset, south west England - Gordon Morris (Commonwealth Journal of Local Governance, 2018)
The research discussed in this paper arose from the writer’s interest in United Kingdom (UK) rural policy, government and governance. Its aims were to: 1) find out the extent to which the participants in the research, many of whom are involved in UK local government, were aware of the non-governmental advisory and support organisations that, from 1909 until 2013, were involved with rural policy; and 2) establish the loci of influence in relation to aspects of rural policy. The data, gathered from interviews and an online questionnaire, suggests that political influence lies primarily with the Conservative Party, whose elected members run the district and county councils. Other sources of influence include the middle and landed classes. There is ambiguity, however. Some clerks and councillors admitted that they do not know where influence lies; suggesting that they, at least, do not believe it lies with them. Awareness of the organisations is unsurprisingly varied according to the participants’ backgrounds. Overall, the data suggests that the more remote organisations were physically from ‘work on the ground’, and the more years that have passed since their closure, the lower the awareness of their existence and work.